MOLECULAR DIAGNOSTICS OF ISOLATES OF FOREST CANKER FUNGI USING POLYMERASE CHAIN REACTION (World Bulletin of Public Health, 2022)
Accurate classification of fungi is important in the diagnosis of pathogenic fungi Several studies have indicated that phenotypic traits cannot be relied upon the diagnosis of fungi, as it requires sufficient experience in the field of classification of fungi, especially when dealing with fungal groups that are very similar to each other in addition to that it requires a great deal of time and effort, as well as the influence of the sizes, shapes and colors of spores by various environmental factors (Huang et al. 2016).